Follow-up of Investments in Algerian Law: How Effective is the New Law No. 22-18? - ABID, Abdelmoumen (Journal of Human Sciences, 2023)
Under the new Law No. 22-18 the registered investments in Algeria benefit from many of the material advantages granted to investors as incentives for the purpose of achieving and then completing their investments to become of added value to the national economy. In return for these advantages-benefits, these investors must fulfill their pledged obligations to the State. This paper asks about the effectiveness of the mechanisms established under the new Investment Law and related implementing texts, in particular Executive Decree No. 22-303, which aims to follow up on these investments as one of the administration’s subsequent methods of oversight.